Social Media Adoption and Innovation on Culinary MSMEs Performance Through Competitive Advantages During COVID-19 - Pertiwi, Ninda Annisa Mufida; Setiawan, Margono; Rahayu, Mintarti (International Journal Labs, 2022)
Background: During the COVID-19 pandemic, the business environment and competition for culinary MSMEs in Surabaya have been more active. Adopting social media is a crucial competitive instrument for Surabaya's MSMEs in the food industry to endure and adjust with the COVID-19 epidemic. Product innovation can also help the production of product value, which is essential to the performance of MSMEs. In order to be able to fully explain how the use of social media and innovation impacted the performance of culinary MSMEs in the city of Surabaya during the COVID-19 epidemic, a set of competitive advantage variables was chosen. Aim: Examining the effects that innovation and the use of social media may have on the Surabaya City culinary MSMEs' ability to compete. Method: Based on established culinary MSME sample criteria, researchers assessed the use of purposeful sampling. 120 respondents completed questionnaires for the purpose of gathering the study's primary data, which was then analyzed using the SEM-PLS analytic method and the Smart PLS 3.0 software. Findings: The adoption of social media by effective MSMEs can increase the competitive advantage of MSMEs so that from the competitive advantages possessed by MSMEs, it can result in the achievement of better MSME performance.